Employee perspectives on value realization from data within data-driven business models - Matthias Förster; Bastian Bansemir; Angela Roth (Electronic Markets, 2022)
Firms are innovating data-driven business models (DDBMs) to realize value from data. Yet, making DDBMs work is challenging, and DDBMs often fall short of expected value realization. One reason for this shortfall is that firms do not know how employees, who decisively influence a DDBM's value realization, view this complex and multi-facetted topic. We think it is necessary to understand the employees' perspectives, the dimensions that build these perspectives and the characteristics employees are particularly interested in regarding value realization from data. We address this research gap by applying the Q-methodology to examine the perspectives among 70 employees across twelve DDBMs at a German automotive manufacturer. This yields eight perspectives, e.g., data advocacy, data caution or data practical. By exploring these perspectives, we provide a first groundwork on how employees view and appraise value realization from data which adds to the strive for mastering value realization from data within DDBMs.
Keywords: L62; O32; 620; Data-driven business models; Value realization from data